2020
DOI: 10.1016/j.jgo.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polypharmacy and inpatient hospitalization among older adults with cancer treated with intravenous chemotherapy

Abstract: Objectives: Polypharmacy (≥5 concurrent medications) is common among older patients with cancer (48%-80%) and associated with increased frailty, morbidity, and mortality. This study examined the relationship between polypharmacy and inpatient hospitalization among older adults with cancer treated with intravenous (IV) chemotherapy. Materials and Methods: The main data source was the Surveillance, Epidemiology, and End Results-Medicare linked files. Patients (≥65 years) were included if they were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
1
17
2
Order By: Relevance
“…Other reasons also included gastrointestinal, cardiac and pulmonary events (respectively 9%, 8% and 6%). Lu-Yao et al also demonstrated that polypharmacy (>5 medications) was associated with a higher rate of unplanned hospitalizations in patients treated with chemotherapy, although this was not confirmed in our study [23].…”
Section: Discussioncontrasting
confidence: 88%
“…Other reasons also included gastrointestinal, cardiac and pulmonary events (respectively 9%, 8% and 6%). Lu-Yao et al also demonstrated that polypharmacy (>5 medications) was associated with a higher rate of unplanned hospitalizations in patients treated with chemotherapy, although this was not confirmed in our study [23].…”
Section: Discussioncontrasting
confidence: 88%
“… 40 In older patients with cancer receiving chemotherapy, polypharmacy is associated with dramatic increases (up to 114%) in unplanned hospitalizations. 41 , 42 In the ELCAPA cohort, potential DDI (but not polypharmacy) was independently associated with the risk of unplanned hospitalization, suggesting that much of the risk may be attributable to DDI and suggesting an opportunity for further study and intervention. In our study, the risk of potential major DDI increased 39% with each additional medication (prescription or nonprescription), and the risk of an interaction with cancer treatment increased 12%, indicating a need to critically evaluate the utility and safety of every medication at the start of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is most common among older adults [17,18], who are more vulnerable to comorbid conditions [19] and polypharmacy which further complicates their cancer experience [20,21]. Amongst all people living with cancer, 90% access cancer information online [22], with older adults often citing a preference for their caregivers to acquire online information for them [23,24] to inform their healthcare decisions [25,26].…”
Section: Introductionmentioning
confidence: 99%